From Education to Family Networks: Analyzing Demographic and Socio-Economic Drivers of Migration Intentions in Bangladesh Under the NELM Framework - Shawon Talukdar; Habiba, Umme (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2025)
This study examines the impact of demographic and socioeconomic factors on migration intentions in Bangladesh within the New Economic Theory of Migration (NELM) framework. Using logistic regression and cluster analysis on convenience survey data, findings show that higher education (OR = 1.45, p < 0.01) and higher income (OR = 1.20, p < 0.05) significantly increase migration intentions. Having family members who migrated also elevates intentions (OR = 1.60, p < 0.01). Interaction effects reveal distinct patterns among younger-educated individuals (p < 0.05). Cluster analysis identifies younger, lower-income, and educated individuals as most likely to migrate, highlighting NELM’s policy relevance.